Baseball performance via the lens of anthropometric testing, fitness metrics, and statistics: a longitudinal cross-sectional study. Issue 2 (20th March 2021) - Papadakis, Zacharias; Padgett, Robert N.; Stamatis, Andreas; Karasch, Richard A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Anthropometric testing (AT) and fitness metrics (FM) are contributing factors for success in sports. Limited evidence exists regarding longitudinal baseball AT or FM roles on baseball performance statistics (PS). AT, FM, and PS associations were examined for 5 yr to create a performance model. Methods: Eighty collegiate Division I players participated in this study. Height, mass, and body fat percentage (BF%) were selected as AT variables of interest. Grip strength (GS), one repetition maximum squat (1RMSQ), and vertical-jump height were selected for FM. Batting average percentage (AVG), slugging percentage (SLG), on-base percentage (OBP) baseball statistics were selected as offensive PS. Earned run average (ERA), batting average against percentage (B/AVG), and strike-out per innings pitched for 9 innings (SO/IP)*9 were selected for defensive PS. Results: Offensive (r=−0.15, P <0.005; rs =−0.17, P <0.001) and defensive (r=−0.253, P <0.001; rs =−0.314, P <0.001) statistics correlated with BF%. Offensive (r=0.26, P <0.001; rs =0.43, P <0.001) and defensive (r=0.39, P <0.001) statistics correlated with GS. Offensive (r=0.26, P <0.001; rs =0.43, P <0.001) and defensive (r=0.27, P <0.001) statistics correlated with 1RMSQ. Offensive statistics AVG (R 2 =0.48) and SLG (R 2 =0.46) were explained by 1RMSQ. For defensive statistics, 1RMSQ was the best fit for (SO/IP)*9 (R 2 =0.43) and B/AVG (R 2 =0.52), and GS was the best fit for ERA (R 2 =0.39). Squat and time interaction for B/AVG was significant ( P =0.04). Conclusions: Baseball PS are associated with 1RMSQ and GS. Time moderates the effect of squat training on B/AVG. Pitchers need to include squats to lower their B/AVG. Coaches may focus on improving such FM variables and consider the time effect on selected FM that may affect PS. Level of Evidence: Level IV